"Diagnosis on the Dock" project: A proactive screening program for diagnosing pulmonary tuberculosis in disembarking refugees and new SEI model. (May 2021) - Pampaloni, Alessio; Locatelli, Maria Elena; Venanzi Rullo, Emmanuele; Alaimo, Salvatore; Cosentino, Federica; Marino, Andrea; Moscatt, Vittoria; Scuderi, Daniele; Puglisi, Sara; Lupo, Gaetano; Celesia, Benedetto Maurizio; Pintaudi, Sergio; et al.
Highlights: Between 2016 and 2017 about 300.805 refugees arrived on Sicily's coasts from Africa. Refugees embark on a long journey filled with violence, imprisonment and starvation. 17% of refugees with fever and cough were affected with pulmonary tuberculosis. About 4500 people will be saved from tuberculosis exposure in the next thirty years. Abstract: Objective: From 2011 to 2017, the total number of refugees arriving in Europe, particularly in Italy, climbed dramatically. Our aim was to diagnose pulmonary TB in migrants coming from the African coast using a clinical-based port of arrival (PoA) screening program. Methods: From 2016 to 2018, migrants coming via the Mediterranean Route were screened for body temperature and the presence of cough directly on the dock: if they were feverish with productive cough, their sputum was examined with NAAT; with a dry cough, they underwent Chest-X-ray (CXR). Those migrants with positive NAAT or CXR suggestive for TB were admitted to our ward. In addition, we plotted an SEI simulation of our project to evaluate the epidemiological impact of our screening. Results: Out of 33.676 disembarking migrants, 314 (0.9%) had fever and cough: 80 (25.47%) with productive cough underwent NAAT in sputum, and 16 were positive for TB; 234 (74.52%) with dry cough had a CXR examination, and 39 were suggestive of TB, later confirmed by mycobacterial culture. The SEI-new model analysis demonstrated that our screening program significantly reduced TB spreading all over the country. Conclusions: For possible future high migrant flows, PoA screening for TB has to be considered feasible and effective in decreasing TB spreading.